2017
DOI: 10.1002/jat.3498
|View full text |Cite
|
Sign up to set email alerts
|

Untargeted metabolomics of neuronal cell culture: A model system for the toxicity testing of insecticide chemical exposure

Abstract: Toxicity testing is essential for the protection of human health from exposure to toxic environmental chemicals. As traditional toxicity testing is carried out using animal models, mammalian cell culture models are becoming an increasingly attractive alternative to animal testing. Combining the use of mammalian cell culture models with screening-style molecular profiling technologies, such as metabolomics, can uncover previously unknown biochemical bases of toxicity. We have used a mass spectrometry-based unta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 70 publications
0
3
0
Order By: Relevance
“…Such an approach, for the prediction of toxic effects on biochemical pathways, is not only essential for enhancing our understanding of toxicology, but is also essential for the reduction of the use of animals in toxic chemical testing. As previously advocated, a ‘whole of cell’ metabolomic approach has benefits over individual biomarkers derived from animal studies, because it allows changes across entire biochemical pathways to be profiled, giving a more complete picture of the effects of toxins [ 36 ]. Future studies should compare the metabolic effect of methamphetamine on a human neuronal cell line with that on the rat B50 neuronal cell line.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such an approach, for the prediction of toxic effects on biochemical pathways, is not only essential for enhancing our understanding of toxicology, but is also essential for the reduction of the use of animals in toxic chemical testing. As previously advocated, a ‘whole of cell’ metabolomic approach has benefits over individual biomarkers derived from animal studies, because it allows changes across entire biochemical pathways to be profiled, giving a more complete picture of the effects of toxins [ 36 ]. Future studies should compare the metabolic effect of methamphetamine on a human neuronal cell line with that on the rat B50 neuronal cell line.…”
Section: Discussionmentioning
confidence: 99%
“…Very few studies have used this approach for the assessment of neurotoxicity [ 35 ]. We have recently demonstrated that gas chromatography–mass spectrometry (GC–MS) metabolomic analysis could be used to generate meaningful biochemical data about the effects of a high dose of insecticides on a continuous cell line, the rat B50 neuroblastoma [ 36 ]. The aim of this study was therefore to determine whether this same model could be applied to the study of methamphetamine toxicity, and to generate biologically relevant data.…”
Section: Introductionmentioning
confidence: 99%
“…Some authors restrict the metabolome to the set of endogenous metabolites [ 6 , 7 , 8 ], although the exogenous metabolites (e.g., drugs and body microbiota) also play an important role in an organism’s physiology or pathophysiology [ 9 ]. In fact, the metabolome can be divided into four categories: (i) the intracellular metabolome (or endometabolome), which includes all metabolites produced by each cell type, tissue, or organism [ 10 , 11 ]; (ii) the extracellular metabolome (or exometabolome), which refers to the metabolites secreted or consumed by the cells [ 11 , 12 ]; (iii) the microbial metabolome produced by the microbiota [ 10 , 13 ]; and (iv) the xenometabolome, which includes the metabolites derived from xenobiotics, pollutants, and diet [ 10 , 14 ].…”
Section: What Is the Metabolome?mentioning
confidence: 99%